Upaya Mengatasi Masalah Perlindungan Anak Korban Kekerasan - Novida Anggraeni; Disson Muhammad F; Fitria Agustin (Public Administration Journal (PAJ), 2017)
Child protection up to now given special attention and became a very important issue. The basic point is addressed in the context of child protection not only to create a system of rules but to a proper service and can be accepted by children. This issue has been progressing, not only in the interests of protecting, but also promote the welfare of children and ensure the best for the childs needs. Fulfillment of child welfare protection approach of the various aspects that have been cultivated spotty. Admittedly, that although the child protection policy and child welfare policy has to accommodate a variety of interests, but the implementation is still not bring maximum results.